Perbandingan Manifestasi Klinis Penderita Demam Berdarah - Zul Fikar Ahmad; Nadila Salsabila Mongilong; Laksmyn Kadir; St. Surya Indah Nurdin; Dewi Rahmawaty Moo (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Dengue hemorrhagic fever has spread throughout the region, especially in tropical and warm climates. Dengue fever has become a global health problem and causes outbreaks almost every year. This study aims to compare the clinical manifestations of DHF patients in pediatrics and adults. This study used a health center-based cross-sectional approach and used secondary data on DHF sufferers from 2019-2022 at the Tutuyan Health Center, namely 72 sufferers. Clinical manifestations of fever are symptoms that generally appear in patients with DHF (100%), and headaches (72.2%), vomiting (40.3%), nausea (34.7%). Meanwhile, the few symptoms found were abdominal pain (15.3%), aches (15.3%), rash (11.1%), joint pain (9.7%), and seizures (8.3%). Abdominal pain, joint pain, aches, nausea, and vomiting are commonly found in adults, while rashes and seizures are commonly found in pediatrics. More efforts are needed to strengthen national programs and thereby reduce the morbidity, mortality, and social and economic burden generated by DHF outbreaks and epidemics